Pengaruh Motivasi Dan Budaya Organisasi Terhadap Kepuasan Kerja Karyawan Pada PT. Indo Acidatama TBK Kemiri Kebakkramat Karanganyar Tahun 2015 - WULANDARI, SITI, Dr. Wafroturrohmah, SE., MM (2015)
The purpose of this study was to determine: 1) The effect of motivation on job satisfaction of employees at PT. Indo Acidatama Tbk Pecan Kebakkramat Karanganyar 2015. 2) The influence of organizational culture on job satisfaction of employees at PT. Indo Acidatama Tbk Pecan Kebakkramat Karanganyar 2015. 3) The influence of organizational culture on motivation and job satisfaction of employees at PT. Indo Acidatama Tbk Pecan Kebakkramat Karanganyar 2015. This associative quantitative research took place at PT. Indo Acidatama Tbk Pecan Kebakkramat Karanganyar. A population of 362 employees, with 177 employees sample, data collection techniques using the questionnaire technique. The data analysis technique used to test the hypothesis is multiple linear regression analysis, t test, F test, the coefficient of determination, the relative contribution and donations effectively. Results of regression analysis to obtain regression line is Y = 10.966 + 0,365X_1 + 0,388X_2. The equation shows that the two independent variables namely motivation and organizational culture together affect the job satisfaction of employees. The conclusion of this study were: 1) There is a positive effect of motivation on job satisfaction of employees at PT. Indo Acidatama Tbk.Hal is shown on the t test results obtained t_hitung> t_tabelyaitu 4.601> 1.973 and the significance value <0.05 is 0,000dengan effective contribution amounting to 21.29% .2) There was a positive influence of organizational culture on job satisfaction of employees at PT. Indo Acidatama Tbk. It is shown from the t test results obtained t_hitung> t_tabelyaitu 4.176> 1.973 and the significance value <0.05 is 0.000 to 9.41% effective contribution. 3) There is a positive influence of organizational culture on motivation and job satisfaction of employees at PT. Indo Acidatama Tbk. It is shown from the analysis results obtained F_ F test (count)> F_tabel ie 38.354> 3.90 and a significance value <0.05 is 0.000. 4) The coefficient of determination R2 of 0.307 which indicates that the motivation and organizational culture together affect the job satisfaction of employees at PT. Indo Acidatama Tbk amounted to 30.7% and the remaining 69.3% of employee satisfaction is influenced by other factors not examined in this study such as leadership, communication, education, and others.